P–463 Patients undergoing elective and onco-fertility preservation respond similarly to controlled ovarian stimulation for fertility preservation. (6th August 2021) - Kira, A; Hentschke, M; Fontour. d. Vasconcelos, N; Deven. Trindade, V; Colombo, T; Petracco, A; Pinheir. d. Costa, B E; Badalotti, M
Abstract: Study question: Is the oocyte vitrification response different in patients undergoing elective and onco-fertility preservation? Summary answer: Patients undergoing elective and onco-fertility preservation seem to respond similarly to controlled ovarian stimulation for fertility preservation. What is known already: Age persists as the factor with the most significant impact on the prognosis of female fertility. The ovarian reserve can also be threatened by surgical, radiotherapy or chemotherapy procedures. Thus, maternity delay and the increased incidence of malignant diseases are the most jeopardizing conditions for reproductive potential in women. Studies are still conflicting about oocyte freezing results in patients with and without cancer. Some studies suggest worse outcomes in patients with cancer regarding the number of mature vitrified oocytes when compared to healthy patients whether others show similar response to the ovarian stimulation for fertility preservation in both groups. Study design, size, duration: Observational, cross-sectional, and historical study using data from 367 who underwent oocyte vitrification from a Reproductive Medicine Center, between 2009 and 2018. Participants/materials, setting, methods: Patients were divided into an elective group (EG; n = 327) and an onco-fertility group (OFG; n = 40). Data were presented as mean ± standard deviation or median and interquartile range (IQR) and absolute and relative frequencies. Chi-square test, Student's t-test, or Mann-Whitney test were applied. Generalized linear models were used to control confounding factors. Data were adjusted by women age, FSH, and GnRH protocol. The null hypothesis was rejected when p < 0.05. Main results and the role of chance: Patients age in OFG was significantly lower compared to EG (31.3±5.8 vs. 37.0 ±2.9 years; p < 0.01) and also FSH measurement (4.0 [3.3 – 6.2] vs. 9.0 (5.4 – 9.9) mIU/mL; p < 0.01). The presence of a partner was significantly higher in OFG (25 [62.5%] vs. [19.9%]; p < 0.001). GnRH antagonist protocol was used in 80.1% of cycles, and FSH-r was used in 80.4% of cycles. Letrozole was added for 20 breast cancer patients (74%). When adjusting data for age, FSH and Gonadotropin-releasing Hormone (GnRH) protocols, no significant difference in the number of vitrified mature oocytes between the two groups were observed (6.0 [3.0–11.0] vs. 7.0 [3.0–12.0]; p = 0.11). Limitations, reasons for caution: The number of women in the OFG was lower than the EG group. The OFG was composed of different types of tumors in different locations and stages. Thus, it can be questioned whether any patient with a more aggressive tumor might have had a negative impact on the results. Wider implications of the findings: Healthy patients and patients with cancer seem to respond similarly to ovarian stimulation for fertility preservation. The extensive number of cycles performed for EG in contrast to OFG leads to a reflection on patients who are still not referred for reproductive counseling after a cancer diagnosis. Trial registration number: Not applicable